Pengaruh Kualitas, Fasilitas, dan Harga terhadap Kepuasan Pelanggan Pengiriman Shopee Express di Kalangan Mahasiswa - Na’ajla Andiza Putri; Alya Nurjanah; Yulia Putri Wulandari; Rafida Rahma Aulia; Siti Sahara (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study aims to evaluate the effect of quality, facilities, and price on customer satisfaction with Shopee Express delivery among students. The research was conducted using a survey method with a sample of 126  students who had used the Shopee Express delivery service. Data was collected through questionnaires and regression analysis related to the dependence of one variable on another variable (the effect of service quality and price on consumer satisfaction at the Shopee Ekspress freight forwarding service company). The results showed that quality, facilities, and price had a positive and significant impact on customer satisfaction. The managerial implication of this research is that companies need to focus on improving the quality, facilities, and price of delivery services to increase customer satisfaction and maintain their market share among students.